<span>The process of solving the inequality will be:
-2(5 - 4x) < 6x - 4
8x - 10 < 6x - 4
-6 < -2x
x > 3
This is in accordance to the rule of solving inequalities which states that whenever we multiply or divide by a negative number while solving an inequality, we must reverse the inequality sign.
The last option is correct.</span>
The answer is 9.
I hope that helps you!
Answer:
the first one and the third one, negative three's don't count so don't put those in.
Step-by-step explanation:
-6 ÷ -2 = 3
4 - (-1) = 5
(-1)(-3)= 3
(-2) - 1 = -3
15 ÷ -5 = -3
4÷ 1 = 4
Answer:
∠ABC= 82°
∠ACB= 82°
∠BAC= 16°
Step-by-step explanation:
∠ABC +∠ACB +∠BAC = 180° (∠ sum of △ABC)
(5x -3)° +(5x -3)° +(x -1)°= 180°
5x -3 +5x -3 +x -1= 180
11x -7= 180 <em>(</em><em>simplify</em><em>)</em>
11x= 180 +7 <em>(</em><em>+</em><em>7</em><em> </em><em>on</em><em> </em><em>both</em><em> </em><em>sides</em><em>)</em>
11x= 187
x= 187 ÷11
x= 17
∠ABC
= (5x -3)°
= [5(17) -3]°
= 82°
∠ACB
= ∠ABC
= 82°
∠BAC
= (17 -1)°
= 16°
Alternatively,
∠BAC
= 180° -82° -82°
= 16°
Answer:
14
Step-by-step explanation:
14 becuase if it was 3 times as many as Kate got then you would have to do the opposite than what it is asking so you would have to divide and you would get 14
Ali do be famous doe lol